Health Behavior Change and Complementary Medicine Use: National Health Interview Survey 2012 - Felicity L Bishop; Romy Lauche; Holger Cramer; Jonquil W Pinto; Brenda Leung; Helen Hall; Matthew Leach; Vincent CH Chung; Tobias Sundberg; Yan Zhang; Amie Steel; Lesley Ward; et al. (Medicina, 2019)
Background and objectives: Complementary and alternative medicine (CAM) use has been associated with preventive health behaviors. However, the role of CAM use in patients’ health behaviors remains unclear. This study aimed to determine the extent to which patients report that CAM use motivates them to make changes to their health behaviors. Materials and Methods: This secondary analysis of 2012 National Health Interview Survey data involved 10,201 CAM users living in the United States who identified up to three CAM therapies most important to their health. Analyses assessed the extent to which participants reported that their CAM use motivated positive health behavior changes, specifically: eating healthier, eating more organic foods, cutting back/stopping drinking alcohol, cutting back/quitting smoking cigarettes, and/or exercising more regularly. Results: Overall, 45.4% of CAM users reported being motivated by CAM to make positive health behavior changes, including exercising more regularly (34.9%), eating healthier (31.4%), eating more organic foods (17.2%), reducing/stopping smoking (16.6% of smokers), or reducing/stopping drinking alcohol (8.7% of drinkers). Individual CAM therapies motivated positive health behavior changes in 22% (massage) to 81% (special diets) of users. People were more likely to report being motivated to change health behaviors if they were: aged 18−64 compared to those aged over 65 years; of female gender; not in a relationship; of Hispanic or Black ethnicity, compared to White; reporting at least college education, compared to people with less than high school education; without health insurance. Conclusions: A sizeable proportion of respondents were motivated by their CAM use to undertake health behavior changes. CAM practices and practitioners could help improve patients’ health behavior and have potentially significant implications for public health and preventive medicine initiatives; this warrants further research attention.